Willingness of reproductive‐aged women in a Nigerian community to accept human papillomavirus vaccination for their children. Issue 10 (26th August 2015) - Morhason‐Bello, Imran O.; Wallis, Selina; Adedokun, Babatunde O.; Adewole, Isaac F.
Abstract Aim The aim of this study was to determine the willingness of reproductive‐aged women in a Nigerian community to allow human papillomavirus (HPV) vaccination in their children and the associated factors with this decision. Material and Methods A multistage household survey of 1002 women who participated in the HPV Vaccine and Cervical Cancer Prevention Survey from 26 August to 29 September 2012 at Ibadan North Local Government Area, Mokola Ibadan, Nigeria. Descriptive, bivariate and multivariable analyses were performed, and statistical significance was set at 95% confidence level (CI). Results There was high willingness (88.6%) to vaccinate, and this attitude was associated with previous history of genital discharge or sores (adjusted odds ratio, 1.91; 95%CI, 1.05–3.45), and knowledge that cervical cancer is preventable (adjusted odds ratio, 1.67; 95%CI, 1.07–2.59). On the likely acceptability of Nigerian HPV vaccine policy, about two‐thirds strongly agreed to its incorporation into the routine immunization program (66.9%), it being free (66.7%) and mandatory (64.3%), amongst other factors. The commonest concerns raised were cost/expenses (10.2%), that it might encourage promiscuity (9.9%), or stimulate early sexual debut (6.7%), and fear of infertility (6.3%). Conclusion This study found that the majority of Nigerian women are willing to vaccinate their children against HPV infection and would prefer free universal HPV vaccination with regulation to ensure better uptake. The concerns expressed would need to be addressed by policy‐makers to increase its acceptability.